2019
DOI: 10.5114/reum.2019.83235
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sexual dysfunction in women with systemic lupus erythematosus and its related factors

Abstract: ObjectivesSystemic lupus erythematosus (SLE) affects all body organs. This disease has marked physiological, mental, and cognitive effects on the patient and results in sexual dysfunction, depression, and decreased self-confidence. This study was conducted to compare sexual function, depression, anxiety, stress, and the related factors in women suffering from SLE.Material and methodsIn this cross-sectional study, 340 women (170 with SLE and 170 healthy) aged 18–49 years were investigated. Convenience sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 21 publications
1
21
0
1
Order By: Relevance
“…The proportion of SLE patients reporting SD across studies ranged between 15% to 85.9%. 1215 Shen et al. suggested that the frequency of self-reported impaired sexual function among SLE patients was significantly higher than healthy individuals (64.10% vs. 35.7%, p < 0.001).…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of SLE patients reporting SD across studies ranged between 15% to 85.9%. 1215 Shen et al. suggested that the frequency of self-reported impaired sexual function among SLE patients was significantly higher than healthy individuals (64.10% vs. 35.7%, p < 0.001).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, multiple regression analysis revealed that age, marital status, disease activity and depression, as evaluated using a demographic questionnaire, SLEDAI, and the Depression, Anxiety, and Stress Scales – 21 Items respectively, had the greatest correlation with the FSFI in women with SLE. 13…”
Section: Discussionmentioning
confidence: 99%
“…About 75% of the study patients and controls, separately, suffered from sexual dysfunction, which is a remarkably higher prevalence than that of other reports. 1215 However; the comparison between Egyptian females and those of other ethnicities could be unfair. Sexuality being a taboo that women fail to express and reveal freely in Arabian societies, there were no equivalent studies to compare with in similar populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In issue no. 1/2019 of the journal Reumatologia , Moghadam ZB et al in the article “Prevalence of sexual dysfunction in women with systemic lupus erythematosus and its related factors” demonstrated that even young women with systemic lupus erythematosus (SLE), with a median disease duration of less than 10 years and inactive or moderately active disease, are more prone to sexual dysfunction compared to healthy controls (85.9% vs. 26.5%) [1]. Age and disease activity arise as major determinants of sexual dysfunction, whereas this aspect is usually underrated by healthcare physicians.…”
mentioning
confidence: 99%